Building Customer Trust through Satisfaction, Value, and Brand Image: A Study of Coffee Consumers in Indonesia - Setyadi, Dody; Purnamasari, Eva; Malebra, Irawan; Utaminingtyas, Rara Ririn Budi; Kanowahadi, Kanowahadi; Pradita, Arisha Putri (RSF Conference Series: Business, Management and Social Sciences, 2025)
This study is motivated by the increasing competition in the coffee industry, both locally and nationally, making it essential to understand the factors that shape customer trust. The purpose of this research is to analyze the influence of Customer Satisfaction, Customer Value, and Brand Image on Customer Trust among coffee consumers in Indonesia. A quantitative approach was used, involving respondents who are coffee consumers from various regions in Indonesia. Data analysis was conducted using multiple linear regression with the assistance of SPSS. The findings show that all three independent variables have a positive and significant effect on Customer Trust, with Brand Image having the most dominant influence, followed by Customer Value and Customer Satisfaction. This indicates that a positive perception of the brand, perceived value, and customer satisfaction collectively form strong trust in coffee products. This study provides practical implications for coffee industry players to strengthen brand image, deliver tangible added value, and maintain customer satisfaction to build trust-based loyalty. It also opens opportunities for further research by adding mediating or moderating variables within the context of coffee consumer behavior in Indonesia.